FORMULASI BISKUIT TINGGI SERAT BERBASIS TEPUNG UBI JALAR UNGU DAN TEPUNG KULIT PISANG KEPOK SEBAGAI CAMILAN ALTERNATIF BAGI PENDERITA SEMBELIT - jeltiani, skolastika; Hudha, Mohammad Istnaeny (Teknik Kimia ITN Malang, 2025)
Constipation is a condition of lack of peristaltic movement in the large intestine, resulting in difficulty in the process of defecating because it is retained in the large intestine for a long period of time. One way to overcome constipation is by consuming high-fiber biscuits. The purpose of this study was to determine the best formulation of variations of purple sweet potato flour and banana peel flour with the addition of tomato pulp concentration. This study used a Completely Randomized Design method with 5 levels of treatment with the formulation of purple sweet potato flour and banana peel flour, F1 (50%: 50%), F2 (55%: 45%), F3 (60%: 40%), F4 (65%: 35%), F5 (70%: 30%) and tomato pulp concentrations of 15%, 25%, 35%. Organoleptic testing using SPSS statistical analysis if the ANOVA results at the 5% level show a significant difference, further testing will be carried out with Duncan's Multiple Range Test (DMRT). The results of the hedonic test showed that the best formulation was F3 (60%:40%) with a tomato pulp concentration of 15%. In addition, the water content in the biscuits met the SNI standard <5%. The conclusion of this study was that there was a significant difference in the formulation of purple sweet potato flour and kepok banana peel flour with the addition of tomato pulp concentration on organoleptic tests and water content.